Predicting the hydrolytic breakdown rates of organophosphorus chemical warfare agent simulants using association constants derived from hydrogen bonded complex formation events. Issue 6 (3rd June 2021) - Ellaby, Rebecca J.; Chu, Dominique F.; Pépés, Antigoni; Clark, Ewan R.; Hiscock, Jennifer
ABSTRACT: Organophosphorus (OP) chemical warfare agents (CWAs) represent an ongoing global threat, through either purposeful environmental release or the need to dispose of historic stockpiles. This presents a need for the development of novel decontamination technologies. Due to the toxic nature and legal limitations placed on OP CWAs, the use of appropriate OP simulants that mimic the reactivity but not the toxicity of the agents themselves is vital to decontamination studies. Herein, we show that association constants derived from non-specific hydrogen bonded complexation events may be used as parameters within models to predict simulant reactivity. We also discuss the limitations that should be placed on such data. GRAPHICAL ABSTRACT: uf0001